The Influence of Chest-Knee Position on the Appearance of anal Physical Findings in Comparison with other Clinical Positions during the Examination of Sexual anal Assault Victim - Mohanad S. O. Jaber; Shrouq S. Al-Sabaileh (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Sexual anal assault is an important and critical issue worldwide. Usually the clinical examinationreveals subtle findings to prove the incident of sexual anal assault. Thus for approaching a proper diagnosis, thevictim needs to be examined by a trained and experienced forensic physician who is officially involved in dealingwith such issues.Methods: Prospective study of 82 victims of sexual anal assault transferred by the local prosecutor to the forensicmedicine department.Results: The majority of victims were females (82%), most of them were younger than 18 years (53.8%). Thefindings obtained by other clinical positions regarding the distribution of anal cutaneous folds revealed that(82%) of victims showed normal distribution, and (18%) showed abnormal distribution of the folds. While afterchest-knee positioning (33.3%) of victims showed normal distribution of the anal cutaneous folds and (38.5%)showed abnormal distribution along with (28.2%) of victims showed absence of folds. Regarding inspection ofanal sphincter by other clinical positions; (84.6%) of victims showed normally contracted sphincter and (15.4%)showed less contractility of the sphincter, whilst by chest-knee positioning (35.9%) of victims showed normallycontracted sphincter with the majority of victims (64.1%) showed abnormal contraction. Concerning injuries in theanal region represented mainly by contusions and abrasions; they were noticed only in (12.8%) of victims by otherclinical positions, while were present in (29%) of victims examined with chest-knee position.Conclusions: During the clinical examination of victims of sexual anal assault, and in comparison with otherclinical positions used, the application of chest-knee position showed overall more conspicuous physical findings,especially regarding the distribution of anal cutaneous folds, the inspected degree of contractility of anal sphincter,and the presence of injuries in the anal region represented mainly by contusions and abrasions.